Tibet protesters removed from Olympic Equestrian in Hong Kong. (Tibetan Review: The Monthly Magazine on all Aspects of Tibet, 2008)
The article reports on the removal of a group Tibetan protesters during the dressage round of the three-day Olympic equestrian competition in Hong Kong on August 8, 2008. According to reports, all protesters are removed and banned from the venue although not arrested. Christina Chan and fellow student were caught sneaking a Tibetan flag which was hidden under a Canadian flag. Other demonstrations are also highlighted.